Diagnostic accuracy for drug detection using liquid chromatography/mass spectroscopy in overdose patients. Issue 1 (30th January 2020) - Yagihashi, Gen; Tarui, Takehiko; Miyagi, Hiroyuki; Ohnishi, Hiroaki; Watanabe, Takashi; Yamaguchi, Yoshihiro
Abstract : Aim: Information about the causative drugs is essential for appropriate treatment for drug overdose, but patients sometimes cannot provide information about overdosed drugs owing to disturbed consciousness or an unwillingness to cooperate with treatment. The purpose of this study was to decide whether liquid chromatography/mass spectroscopy (LC/MS) is useful as a detection method for overdosed drugs. Methods: Overdose patients ( n = 279) treated in our facility were retrospectively studied. Specimens from gastric lavage, blood serum, and urine were tested using LC/MS. The matching rates between drugs overdosed and those detected by LC/MS were evaluated; LC/MS and Triage DOA R were also compared. Data are shown as means. Results: Patients overdosed on 3.2 kinds of drugs and were transferred to our hospital 4.6 h after. Overall 3.5 kinds of drugs were detected by LC/MS, and 2.4, 1.9, and 2.2 kinds were from the stomach, blood, and urine, respectively. Matching rate among the ingested drugs (kinds of drugs matched/ones ingested) was the highest in the gastric samples (0.56), and the lowest in the urine samples (0.46) ( P < 0.01). In addition, the matching rates among the detected drugs (kinds of drugs matched/ones detected) were as high as 0.74 and 0.78 in the gastric and blood samples, respectively. Comparing the sensitivity and specificity of detection of benzodiazepines and tricyclic antidepressants between LC/MS and Triage DOA R, we found that these two methods were comparable. Conclusion: Liquid chromatography/mass spectroscopy was proven to be an effective method to detect overdosed drugs, especially when there was not enough information about the drugs ingested. Abstract : Liquid chromatography/mass spectroscopy (LC/MS) was proven to be an effective method to detect drugs for overdose patients, especially for drugs that were not detected by other screening methods or when there was no information about overdosed drugs. For treating critical patients with a suspicion of drug overdose under such conditions, clinicians should utilize LC/MS if available, or decide to transfer the patients to higher‐level facilities where LC/MS is available.